The influence of media on shaping consumer boycott behaviour / Farah Hazween Amanah …[et al.]. - Amanah, Farah Hazween; Ab Rashid, Faridah Hanem; Khairul Anuar, Nurliyana Kamilah; Hassan @ Assan, Amirah; Ramlan, Muhammad Azril Izuan (Universiti Teknologi MARA, Negeri Sembilan, 2024)
The Internet was the only medium that allowed the involvement of social relationships but with the advancement of technology creates other tools and also software that make communication easier such as the emergence of mobile applications, where social media connect people all over the world. Advances in technology have beneficial users in many ways and change the lifestyle where it makes users’ daily life more easier and scheduled. In this advanced era of globalisation, access to various media, especially social media for searching and gaining various resources and information is very easy and gives significant impact on various aspects of life where everything is at our fingertips. Media is a medium that can stimulate and influence the attitude and also behaviour of individuals in all aspects of human life. The media, especially social media, is not only an information channel to obtain entertainment and knowledge but also shapes various behaviours, personality development, and further empowers individuals whether in a positive direction or vice versa. Mass media developed from mouth spread information from one personto others where with the aid of technology lead to the emerging of social media. Social media is a very sharp weapon in dissemination of information where people can easily post or express their thoughts through writing or even pictures. Social media is one of the tools to spread information, opinions and messages as well as propaganda where social media is very powerful in convincing and influencing mass people.